Multimedia Based Sign Language Learning - Muhammad Rayhan Bustam; Raden Agustiawan; C N Albar; Raiswati Untsa Mega (Jurnal Teknologi Informasi dan Pendidikan, 2021)
Having children with hearing impairment is a great concern for parents in teaching their children to communicate. However, parents tend to have trouble choosing the right approach in teaching children with hearing impairment to not feel lazy and bored quickly in learning. This research aims to create an interactive sign language learning application based on the BISINDO sign language system as an alternative learning media for children with hearing impairment to increase their learning motivation. The application was made to support children with hearing impairment in understanding sign language, starting from recognizing letters, numbers, basic and greeting words; the application was also made as an interactive software equipped with various supporting features such as videos, animations, to trivia quizzes. This research used descriptive methods with observation and interviews, as well as prototype methods in system development. This study indicates that the application can increase learning motivation for children with hearing impairment and provide supporting instruments for parents in teaching children to communicate. In conclusion, the application is beneficial and has a solution for parents to teach sign language to their children who have a hearing impairment and difficulty digesting learning and lack motivation